2022
DOI: 10.1371/journal.pone.0270960
|View full text |Cite
|
Sign up to set email alerts
|

The effects of electrical stunning on the nervous activity and physiological stress response of a commercially important decapod crustacean, the brown crab Cancer pagurus L.

Abstract: Increasing attention is being paid to the welfare of decapod crustaceans. Legislation exists for their humane slaughter in several countries and this is being debated in others. Electrical stunning may have potential for humane slaughter of crustaceans in some circumstances, although scientific data on the effectiveness of electrical stunning when applied to various species are limited. Assessment criteria for effective stunning have so far been based mainly on behavioural assessments, but these do not always … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…It is possible that single studies can inflate the overall influence of the stressor on the final result. For example, electro‐stunning was only presented in one study (Neil et al., 2022) and had one effect size calculated, but it was among the most influential stressors according to our model outputs (Table 5). The two most impactful stressors, trawling and emersion were represented by three and 31 studies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that single studies can inflate the overall influence of the stressor on the final result. For example, electro‐stunning was only presented in one study (Neil et al., 2022) and had one effect size calculated, but it was among the most influential stressors according to our model outputs (Table 5). The two most impactful stressors, trawling and emersion were represented by three and 31 studies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The methodologies used to electrically stun the C. maenas crabs and the H. gammarus lobsters, and to make neurological recordings, are here summarised and were the same as reported by Albalat et al (2022) and Neil et al (2022), where more detailed descriptions can be found.…”
Section: Methodsmentioning
confidence: 99%
“…This would allow time to take a blood or tissue sample, if required for biological analysis, or for an appropriate procedure for humane slaughter to be applied while the animal is in an insensible state (the concept of the 'stun-to-kill' time). In our previous study of brown crabs (Cancer pagurus) (Neil et al, 2022), lack of either nerve activity or behavioural responses at 4 h after stunning was taken to indicate that the crabs were also killed by this procedure, and this was corroborated by holding intact, electrically-stunned crabs for 24 h, and finding no signs of life. Other findings suggest that some caution needs to be applied to this interpretation.…”
Section: Neuronal Indicators Of Insensibilitymentioning
confidence: 96%
See 2 more Smart Citations